On the accretion of Uranus and Neptune - Brunini, Adrián (2002)
In this paper, we discuss some problems concerning the formation of Uranus and Neptune. We find that the adoption of reduced Hill spheres as the region of close interaction between planetesimals introduces an enhancement of the gravitational cross-sections in previous numerical simulations. We also discuss a way to make possible the formation of Uranus and Neptune on time-scales shorter than the age of the Solar system.